2007
DOI: 10.1007/s00330-007-0634-x
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted imaging in normal fetal brain maturation

Abstract: Diffusion-weighted imaging (DWI) provides information about tissue maturation not seen on conventional magnetic resonance imaging. The aim of this study is to analyze the evolution over time of the apparent diffusion coefficient (ADC) of normal fetal brain in utero. DWI was performed on 78 fetuses, ranging from 23 to 37 gestational weeks (GW). All children showed at follow-up a normal neurological evaluation. ADC values were obtained in the deep white matter (DWM) of the centrum semiovale, the frontal, parieta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
99
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(119 citation statements)
references
References 20 publications
18
99
0
2
Order By: Relevance
“…Given fetal diffusion values and maturation curves obtained between 22 and 36 weeks, our findings of ADC and FA values were comparable with the ones presented by different groups, [20][21][22] though subtle differences between fetuses at 37 weeks of gestation and preterm infants at TEA were reported. 23 No fetal data of T1 values are available.…”
Section: Discussionsupporting
confidence: 72%
“…Given fetal diffusion values and maturation curves obtained between 22 and 36 weeks, our findings of ADC and FA values were comparable with the ones presented by different groups, [20][21][22] though subtle differences between fetuses at 37 weeks of gestation and preterm infants at TEA were reported. 23 No fetal data of T1 values are available.…”
Section: Discussionsupporting
confidence: 72%
“…16 The characteristics of T2 signal intensity and diffusion values change with cerebral maturation. 17 Such maturational alterations are visible in both fetal MR imaging 18,19 and in extra uterine preterm infants. 20,21 Thus, another potential explanation for the presence of DEHSI at term-equivalent age is delayed white matter maturation, rather than diffuse injury.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Indeed, diffusion parameters in the developing brain have been found to vary with water content, cell density, formation of white matter tracts, membrane potential, and myelination. 3,6,21 Progressive decrease of ADC values in fetuses after 30 weeks GA 3 and in preterm and term neonates 19,20,[22][23][24] has been putatively ascribed to a sequence of events making up the "premyelination stage" 25,26 and the initiation of myelination. Premyelination is a complex process that includes a reduction in total water content, a rise in lipid concentration, the proliferation and maturation of oligodendrocyte precursors, and the ensheathment of axons by premyelin.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of preterm neonates, term neonates, and children have shown correlation between decreased ADC and progressive brain maturation. [1][2][3][4][5] These changes precede those seen on conventional MR images and provide early information on tissue organization. 6 1 H-MR spectroscopy is an efficient technique for obtaining noninvasive metabolic information from the human brain and has become a powerful diagnostic tool in the pediatric population, especially for the detection of hypoxic encephalopathy, leukoencephalopathies, and inborn errors of metabolism.…”
mentioning
confidence: 93%